A novel mouse model of sporadic colon cancer induced by combination of conditional Apc genes and chemical carcinogen in the absence of Cre recombinase. (12th March 2019) - Souris, Jeffrey S; Zhang, Hannah J; Dougherty, Urszula; Chen, Nai-Tzu; Waller, Joseph V; Lo, Leu-Wei; Hart, John; Chen, Chin-Tu; Bissonnette, Marc
Abstract: Although valuable insights into colon cancer biology have been garnered from human colon cancer cell lines and primary colonic tissues, and animal studies using human colon cancer xenografts, immunocompetent mouse models of spontaneous or chemically induced colon cancer better phenocopy human disease. As most sporadic human colon tumors present adenomatous polyposis coli ( APC ) gene mutations, considerable effort has gone into developing mice that express mutant Apc alleles that mimic human colon cancer pathogenesis. A serious limitation of many of these Apc -mutant murine models, however, is that these mice develop numerous tumors in the small intestine but few, if any, in the colon. In this work, we examined three spontaneous mouse models of colon tumorigenesis based upon the widely used multiple intestinal neoplasia ( Min ) mouse: mice with either constitutive or conditional Apc mutations alone or in combination with caudal-related homeobox transcription factor CDX2P-Cre transgene — either with or without exposure to the potent colon carcinogen azoxymethane. Using the CDX2 promoter to drive Cre recombinase transgene expression effectively inactivated Apc in colonocytes, creating a model with earlier tumor onset and increased tumor incidence/burden, but without the Min mouse model's small intestine tumorigenesis and susceptibility to intestinal perforation/ulceration/hemorrhage. Most significantly, azoxymethane-treated mice with conditional Apc expression, but absent the Cre recombinase gene, demonstrated nearly 50% tumor incidence with two or more large colon tumors per mouse of human-like histology, but no small intestine tumors — unlike the azoxymethane-resistant C57BL/6J-background Min mouse model. As such this model provides a robust platform for chemoprevention studies. Abstract : Conditional Apc gene expression and treatment with the carcinogen azoxymethane, in the absence of Cre recombinase, provides a novel mouse model of colon carcinogenesis suitable for tumor promotion and chemoprevention studies, with tumor development restricted to the colon.